Peran Orang Tua Dan Keluarga Dalam Menghadapi Tantangan Etika Remaja Kristen Di Era Teknologi Digital - Hendrikson Febri; Amoli Ndraha; Erni Dethan; Korina Sanosa; Piter Imanson Damanik (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
As time advances, digital technology has gradually become contaminated with Christian teenagers. Instead of digital technology helping in the process of accelerating